2016
DOI: 10.1111/1758-2229.12397
|View full text |Cite
|
Sign up to set email alerts
|

Recombination‐prone bacterial strains form a reservoir from which epidemic clones emerge in agroecosystems

Abstract: The acquisition of virulence-related genes through horizontal gene transfer can modify the pathogenic profiles of strains and lead to the emergence of new diseases. Xanthomonas arboricola is a bacterial species largely known for the damage it causes to stone and nut fruit trees worldwide. In addition to these host-specific populations called pathovars, many nonpathogenic strains have been identified in this species. Their evolutionary significance in the context of pathogen emergence is unknown. We looked at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 50 publications
6
76
0
Order By: Relevance
“…Heterogeneous populations of yellow-pigmented nonpathogenic strains from different plants and identified as Xanthomonas by various serological, protein profile, or sequence-based methods could not be assigned to existing pathovars, including those grouping strains from the same host species (42,95,131,133). These strains do not cluster with the pathogenic strains of the host from which they were isolated.…”
Section: Interactions Within the Plant-associated Microbial Communitymentioning
confidence: 98%
See 2 more Smart Citations
“…Heterogeneous populations of yellow-pigmented nonpathogenic strains from different plants and identified as Xanthomonas by various serological, protein profile, or sequence-based methods could not be assigned to existing pathovars, including those grouping strains from the same host species (42,95,131,133). These strains do not cluster with the pathogenic strains of the host from which they were isolated.…”
Section: Interactions Within the Plant-associated Microbial Communitymentioning
confidence: 98%
“…These strains do not cluster with the pathogenic strains of the host from which they were isolated. Interestingly, it was noticed that most of these strains belong to the Xanthomonas arboricola species (95). Some represent new separate lineages in known species (42,47) and others form new clades such as the Xanthomonas maliensis species proposed to group the nonpathogenic strains isolated from disinfected rice leaves (131).…”
Section: Interactions Within the Plant-associated Microbial Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some Xaj lineages appeared strongly associated, as in the case of Lin1 frequently isolated with Lin12, and Lin6 recovered simultaneously with Lin11 in all leaf samples. Although, further investigations are important to determine if the xanthomonads diversity within the same walnut host plant and even within the same plant organ, is a mix of bacterial populations colonizing evenly the same host plant and organ, or if it results from the co-colonization of dominant versus lessened xanthomonads populations, it was recently proposed that sympatric populations, as pathogenic and nonpathogenic strains found together on walnut buds, may have important effects on genetic dynamics of new strains emergence (16, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping studies have found a considerable genetic diversity in Xaj , which is reportedly high when compared with the diversity described for other X. arboricola pathovars (5, 11-14). This feature, together with evidence of genomic trade-offs within the species (5, 13, 15, 16), evokes an opportunistic pathogen, even though evidence for environmental reservoirs of Xaj remains poorly characterized (11, 17-19). These data are further supported by the isolation of nonpathogenic strains of X. arboricola , described as phylogenetically heterogeneous, and grouping separately from the well-defined clusters of pathogenic Xaj strains (20).…”
Section: Introductionmentioning
confidence: 99%